Fronteiras desiguais: Um exame crítico da participaç\~ao negra interseccionada com sexo na liderança científica brasileira - Tulio Chiarini; Larissa de Souza Pereira; Carla Pereira Silva; Vitor Marinho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
In Brazil, research groups are cataloged by the CNPq in the "Directory of Research Groups" (DGP). Although this database is widely used in academic studies, to date there has been no analysis of black representation in the leadership of these groups. This pioneering study aims to understand black participation intersected with gender in Brazilian scientific leadership, offering important subsidies for the formulation of public policies that promote gender and racial equity in the country's scientific community. In order to examine black participation in research groups, this study relies on microdata from participants, identifying individuals who self-declare as black (preto and pardo).
Keywords: I23; O15; O34; O38; 330; directory of research groups; diversity in science; epistemic injustice; intersectionality; racism; black women